The bill tip organ of the chicken (Gallus gallus var. domesticus). - Gentle, M J (1986)
At the tip of the lower beak of the chicken there were found 15-20 specialised dermal papillae containing large numbers of mechanoreceptors. The Merkel or Grandry corpuscles were situated distally in the papillae and at the papillae base was a collection of Herbst corpuscles. The apex of the papillae, under the scanning electron microscope, appeared as a row of shallow pits on the surface of the beak just inside the mouth. These papillae resemble similar structures seen in other birds and are probably necessary for fine tactile discrimination.